Do life-logging technologies support memory for the past? An experimental study using SenseCam - Sellen, Abigail; Fogg, Andrew; Aitken, Mike; Hodges, Steve; Rother, Carsten; Woodberry, Ken (Proceedings of CHI 2007, 2007)
We report on the results of a study using SenseCam, a “lifelogging” technology in the form of a wearable camera, which aims to capture data about everyday life in order to support people’s memory for past, personal events. We find evidence that SenseCam images do facilitate people’s ability to connect to their past, but that images do this in different ways. We make a distinction between “remembering” the past, and “knowing” about it, and provide evidence that SenseCam images work differently over time in these capacities. We also compare the efficacy of user-captured images with automatically captured images and discuss the implications of these findings and others for how we conceive of and make claims about life-logging technologies.